Lutein and zeaxanthin isomers may attenuate photo-oxidative retinal damage via modulation of G protein-coupled receptors and growth factors in rats - Şahin, Kazım; Gencoglu, Hasan; Akdemir, Fatih; Orhan, Cemal; Tuzcu, Mehmet; Şahin, Nurhan; Juturu, Vijaya (Academic Press Inc Elsevier Science, 2019)
Background: Retina photoreceptor cells are specially adapted for functioning over comprehensive ambient light conditions. Lutein and Zeaxanthin isomers (L/Zi) can protect photoreceptor cells against excessive light degeneration. Efficacy of L/Zi has been assessed on some G protein-coupled receptors (GPCRs), transcription and neurotrophic factors in the retina of rats exposed to incremental intense light emitting diode (LED) illumination conditions. Methods: Forty-two male rats (age: 8 weeks) were randomly assigned to six treatment groups, 7 rats each. The rats with a 3x2 factorial design were kept under 3 intense light conditions (12hL/12hD, 16hL/8hD, 24hL/OhD) and received two levels of L/Zi (0 or 100 mg/kg BW) for two months. Increased nuclear factor-kappa B (NF-kappa B), glial fibrillary acid protein (GFAP), and decreased Rhodopsin (Rho), Rod arrestin (Sag), G Protein Subunit Alpha Transducin1 (Gnat1), neural cell adhesion molecule (NCAM), growth associated protein-43 (GAP43), nuclear factor (erythroid-derived 2)-like 2 (Nrf2), and heme oxygenase 1 (HO-1) were observed in 24 h light intensity adaptation followed by 16 h IL and 8 h D. Results: L/Zi administration significantly improved antioxidant capacity and retinal Rho, Rod-arrestin (Sag), Gnat1, NCAM, GAP43, BDNF, NGF, IG1, Nrf2, and HO-1 levels. However, the levels of NF-kappa B and GFAP levels were decreased by administration of L/Zi. Conclusions: According to these results, L/Zi may be assumed as an adjunct therapy to prevent early photoreceptor cell degeneration and neutralize free radicals derived from oxidative stress. (C) 2019 Elsevier Inc. All rights reserved.
Keywords: Carotenoids; GPCRs; Light-emitting diode; Neurotrophins; Photo-oxidation; Retina